Successful treatment of excessive dose of carbamazepine - Yaylacı, Selcuk (Medknow Publications & Media Pvt Ltd, 2012)
Carbamazepine is used in the treatment of epilepsy; it is also prescribed for treatment of neuralgic pain syndromes and certain affective disorders. Carbamazepine intoxication with suicide attempt is a relatively common clinical problem that can result in coma, respiratory depression, arrhythmia, hemodynamic instability, and death. There is no specific antidote. Multiple-dose activated charcoal and hemodialysis are the main treatment for carbamazepine intoxication. In this paper, we report the case of a 19-year-old woman with excessive dose carbamazepin intoxication and our successful treatment with multiple-dose activated charcoal and hemodialysis.